Movimentos surdos e educação: negociação da cultura surda - Dall'alba, Carilissa (2013)
This work is central to understand how problematic movements deaf as a space of struggle and resistance is redefining deaf come to building a policy of education for deaf guided joints between sign language and deaf culture. To account for this investment research some goals that guided the study: understanding the emergence of movements in deaf education scenario of the deaf; identify different strategies to fight organized by the movement deaf to understand its effects on deaf education in contemporary. To this he joined the field of Cultural Studies in Education, with crossings of the field of Deaf Studies who understand deafness and deaf education from a cultural and linguistic context specific. The empirical corpus study is divided into two groups of materials: narratives of deaf leaders and a set of documents that consider the conditions of possibility for the emergence of a discourse that has been producing movement deaf from other arrangements, other experiments. These sets of documents are: Document "Deaf Education that we Want" 1999 Project Course Letters / POUNDS, Law 10,436 / 5626 and certainly Movement Bilingual School for the Deaf. To the narratives of deaf leaders, collected through interviews, I could track the movement deaf at two, ie, in two outbreaks of analytical power. The first stage focused on the emergence of the fight for the official recognition of sign language in the constitution of deaf identities and the second in the trading strategies of deaf culture in education. You can check in emergencies and in the possibilities of movement history deaf political organization linked with the education of deaf and negotiation of deaf culture in the contemporary scenario.